Analysis of mud filtration properties using factorial design (1995)
Determining the filtration properties of a mud system requires that experiments be run for both the standard API and the high Temperature High Pressure (HTHP) tests at intervals throughout the duration of drilling an oil well. However, cost and hazard considerations cause more emphasis to be placed on the standard API test at ambient conditions, without taking into account the effects of elevated downhole pressures and temperatures on filtration properties. In this work, the factorial design concept was applied to the filtration properties of drilling muds. Different samples of water based bentonitic muds were used for the experimental runs at both Low Temperature - Low pressure (LTLP) and high Temperature - High Pressure (HTHP) conditions. The input variables considered were temperature, pressure, solids content, mud weight and time; while the response variables were fluid loss and cake thickness. The final results are presented in the form of a statistically significant model that enables prediction of filtration properties at both LTLP and HTHP conditions. This method minimizes the inherent risks usually associated with operating filter presses at elevated pressures and temperatures. In addition, it saves time and cost by minimizing the number of experimental runs always required to assess mud quality and maximizes the information obtained from the few experimental runs. This experimental design technique can also be applied to the quality assessment and control of other drilling fluid properties.